1998
DOI: 10.1063/1.368017
|View full text |Cite
|
Sign up to set email alerts
|

Selective epitaxial growth of silicon carbide on SiO2 masked Si(100): The effects of temperature

Abstract: The effect of substrate temperature on the growth rate, crystal grain size, and SiO 2 mask stability in the selective epitaxial growth of silicon carbide deposited from SiH 4 , C 2 H 4 , and HCl 1 on silicon dioxide masked silicon ͑100͒ was examined. Depositing at atmospheric pressure and a Cl/Si input ratio of 50 to achieve good selectivity, increasing the substrate temperature from 950 to 1000°C increased the growth rate and the crystal size, and improved the film's surface morphology, but also enhanced the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0

Year Published

1999
1999
2010
2010

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 8 publications
0
14
0
Order By: Relevance
“…The degradation of the patterns at temperatures above 800°C occurs presumably by decomposition of silicon oxide and formation of volatile SiO. According to Edgar et al, 9 a 284-nm-thick silicon oxide layer was degraded at 950°C. In our experiments, the degradation of the much thinner ͑ϳfew nm͒ oxide layers started at the relatively low temperature of 800°C.…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…The degradation of the patterns at temperatures above 800°C occurs presumably by decomposition of silicon oxide and formation of volatile SiO. According to Edgar et al, 9 a 284-nm-thick silicon oxide layer was degraded at 950°C. In our experiments, the degradation of the much thinner ͑ϳfew nm͒ oxide layers started at the relatively low temperature of 800°C.…”
Section: Resultsmentioning
confidence: 97%
“…7 For selective area epitaxial growth of SiC, conventional chemical vapor deposition has been employed using a submicrometer-thick silicon oxide layer to impede nucleation. 8,9 However, high growth temperatures above 1000°C are required, which resulted in significant degradation of the microstructures. 9 The degradation is more severe for a thinner silicon oxide mask layer, which results in difficulty in making submicron-scale structures.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…One approach is to use selective epitaxial growth on patterned Si substrates followed by lateral epitaxial overgrowth (LEO). Silicon substrates, with dielectric mask materials such as SiO 2 , Si 3 N 4 and AlN, have been tried [1][2][3][4]. Saddow et al [1] reported some preliminary work on the selective epitaxy of SiC on Si using Si 3 N 4 and AlN as masks.…”
Section: Introductionmentioning
confidence: 99%
“…SEG with SiO 2 mask was attempted only for heteroepitaxial growth of the cubic 3C-SiC polytype on Si substrates conducted at low growth temperatures. 4 Until recently, it has been considered impossible to grow electronic-quality single-crystalline homoepitaxial 4H-and 6H-SiC at temperatures below 1450-1500°C. For this reason, investigations of the physics involved in SEG for 4H-and 6H-SiC had to rely upon untraditional hightemperature masking techniques, 5,6 which constrained progress in this direction.…”
mentioning
confidence: 99%